Assessment of the Underlying Causes and Impact of Fires at the Kumasi Kejetia Market - Azumyarn, Joseph Asako; Afour, Solomon Akubire; Agbeshie, Alex Amerh; Boateng, Ausberth Dankwah; Carlis-Paittoo, Benjamin O.; Elizabeth, Kade Mensah; Nasara, Wilfred Wepia (Universitas Negeri Semarang, 2025)
Marketplaces, serving as vibrant hubs of economic activity and social interaction, are susceptible to various fire-related hazards. The market has suffered repeated market fires, causing economic, livelihood, and safety devastation, necessitating thorough research into their underlying causes and impacts. The study employed a mix of research methodologies: a structured questionnaire for the Ghana National Fire Service (GNFS) and the National Disaster Management Organization (NADMO) (experts) and vendors (non-experts), key informant interviews, focus group discussions, direct observations, and the analysis of results using the Chi-square test, in pursuit of some questions. In the course of assessing the underlying causes of fires in the market, the findings have revealed that negligence (RII: 0.65, rank: 1) was a significant cause of fire incidence in the market, followed by accidents (RII: 0.58, rank: 2). Electrical issues were mentioned as the main “other reason” for the fire outbreaks, with over half of the respondents (74) (53.2%) attributing fires to this cause. With respect to the impact, the majority (109) 64.1% of respondents cited the loss of properties as a significant disadvantage of market fires. The majority of the respondents (35) (63.6%) consider support from Non-Governmental Organizations (NGOs) and about (18) 32.7% of respondents emphasized the importance of having insurance as crucial additional measures to address the economic consequences of market fires. Through observations and findings, the researcher recommends proper safety protocols and public education to prevent similar incidents in the future. Also, encouraging vendors to obtain insurance coverage could help mitigate the financial burden they face in the aftermath of such fire incidents and aid in their recovery process.